You Help Me, He Helps You: Dispute Systems Design in the Sharing Economy - Heather Scheiwe Kulp; Amanda L. Kool (Washington University Journal of Law & Policy, 2015)
Kulp and Kool discuss the potential for dispute resolution schemes in a sharing economy, one they argue involves a more efficient use of resources. The sharing economy is at the nexus of fast-paced technology that connects people to previously inaccessible resources to increase local consumption. Kulp and Kool argue that such sharing economies maximize the benefits of ownership by leveraging goods and services into a resource generator allowing increased access to goods and services at a lower-than-market rate. This unique market structure requires a distinct set of laws to address the unique relationships involved, and this Article explores how attorneys can best assist in managing conflicts in a sharing economy.
Keywords: sharing economy; dispute resolution